1986
DOI: 10.1136/jmg.23.6.548
|View full text |Cite
|
Sign up to set email alerts
|

Linkage analysis of polymorphisms within the DNA fragment XJ cloned from the breakpoint of an X;21 translocation associated with X linked muscular dystrophy.

Abstract: SUMMARY Cloning of a DNA segment including the translocation breakpoint in a female with an X;21 translocation and X linked muscular dystrophy has led to identification of three subclones which detect polymorphic markers. The alleles of these markers, XJ1 1, XJ1-2, and XJ2 2, are in strong linkage disequilibrium. Linkage analysis in 31 families with Duchenne or Becker muscular dystrophy has shown recombination within the XJ segment in one case, and recombination of DMD with both the XJ segment and the pERT87 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 33 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…For example, the restriction fragment length has been reported as 12.0 or 9.0 kb for the probe 754 after digestion with a Kunkel et al (1986) for probes pERT87-15, 87-8 and 87-1, Thompson et al (1986) for probe XJI.1, Worton (1987, personal communication) for probe XJ5.1, and Willard et al (1985) for other probes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the restriction fragment length has been reported as 12.0 or 9.0 kb for the probe 754 after digestion with a Kunkel et al (1986) for probes pERT87-15, 87-8 and 87-1, Thompson et al (1986) for probe XJI.1, Worton (1987, personal communication) for probe XJ5.1, and Willard et al (1985) for other probes.…”
Section: Resultsmentioning
confidence: 99%
“…The third indication of a large gene came from family studies in which rflp markers from the P E R T 87 (Fischbeck et al 1986;) and X J (Thompson et al 1986) region were found to segregate with the dmd gene in only 9 5 % of meioses. In 5 %, a recombination event took place in the chromosome interval between the site of m utation and the site of the probe.…”
Section: Cloning Sequences From Within An Xp21 Deletionmentioning
confidence: 99%